Typologie zukunftsorientierter landwirtschaftlicher Direktvermarktungsbetriebe: Eine empirische Analyse in Deutschland; Typology of Forward-Looking Direct Marketing Farms - an Empirical Analysis in Germany - Stefan-Clemens Wille; Marie von Meyer-Hof̈er; Achim Spiller (German Journal of Agricultural Economics (GJAE), 2019)
– Direct marketing of food may enable farmers to generate higher incomes. Originally, direct marketing comprised on farm sales and weekly markets, but it has recently developed into a professionalized marketing approach of various forms. Hereby, the direct marketers differ by marketing channel, the range of products or the number of labour used. Although direct marketing is an important source of income for some farms, only a few studies have addressed a detailed description of direct marketers so far. This research gap is tackled with by an empirical study of 39 direct marketers. A cluster analysis identified 4 types of direct marketers. Some direct marketers try to offer a full range of products, similar to a retail strategy. Others are specialized in selling to specific actors in the value chain, e.g. the retail. Also the results confirm the classic on farm shop to sell mainly its own produce. The typology may provide a useful guidance for direct marketers or regular farmers when structuring their future farm business.
N.A.
Keywords: 330